Faktor-Faktor Resistansi Masyarakat Desa Ngrayun Terhadap Keputusan Menjadi Nasabah Asuransi Prudential Ponorogo - Nursafitri, Eka; Ulya, Husna Ni'matul (Department of Islamic Banking, Faculty of Islamic Economics and Business, Institut Agama Islam Negeri Pekalongan, 2021)
Islamic insurance will have higher demand and high enthusiasm. Therefore, efforts to increase public knowledge about sharia insurance are a strategic issue in the development of sharia insurance. Consumer knowledge is all information owned by consumers about various products or services. Based on the results of interviews with prudential insurance agents, it was stated that there were still few people who had life insurance, all of that because the level of public trust was still low, this was due to their low knowledge of sharia insurance. And when doing promotions there is rejection from the community. From here, marketers must be able to provide knowledge about the benefits and advantages of Islamic insurance. This study aims: 1) to find out how the development of prudential sharia insurance in Ponorogo. 2) to find out the resistance factors of the Ngrayun Village Community to become Ponorogo prudential insurance customers.This type of research uses field research and uses a qualitative approach. Data collection techniques used in this study were interviews (interviews) and documentation. The results of this study are: 1) The development of Prudential Sharia Insurance in Ponorogo has gone up and down, but in the last period it has decreased. Especially in Ngrayun Village, Ngrayun District, the development of prudential sharia insurance is quite difficult because of various factors that influence people's decisions to join as customers. The prudential sharia insurance agent then determines solutions that can be applied in rural areas, especially Ngrayun Village, Ngrayun District. 2) Existing factors based on the results of interviews with consumers who have received socialization or offers from prudential sharia insurance agents in Ngrayun Village, Ngrayun District arise interrelated factors, both from cultural and sub-cultural factors, occupation, age, reference groups and family , as well as location. Of the several factors that have been mentioned above, these factors are closely related to the consumer's decision to become a customer.